Homelessness from the perspective of volunteer care-workers - Hempe, Babalwa (My University, 2021)
The term ‘home’ may be conceived as a space in which an individual or a group of individuals lives, often in a structure, with access to social amenities. It is also denoted by a group relation such as the family or history. Homelessness is a social phenomenon that poses challenges at both institutional and individual levels. As such, homeless people may have to contend with socio-economic problems like unemployment and the housing crisis; additionally, they grapple with individual problems like substance addiction and mental health issues. Many interventions have been developed to tackle the issue of homelessness, but none of them seems as cost-effective and widespread as volunteering, which is the act of helping another or others without expecting any monetary gain or incentive. Therefore, it is necessary to understand the development of altruistic perceptions and how they develop into pro-social behaviour, particularly the manner in which perceptions could influence behaviour that is helpful to the homeless population in the Johannesburg city centre. The study found that the participants’ willingness to volunteer was not deterred by the negative thoughts they had about the homeless people they helped. However, they reported that their willingness to help tended to wane when the help was of a charitable nature and this is when their perceptions determined whether or not they were willing to give donations to the homeless on the streets. The study found that participants freely assisted to the homeless people they deemed to be in the vulnerable group, for example, families, women, children and the elderly because of societal expectations. On the other hand, the participants indicated that they were less willing to provide charity to men whom they labelled criminal or substance addicts. In this case, they were willing to help in other ways such as fostering study groups, soup kitchens and the provision of health care. Though the participants’ negative perceptions often made them hesitant to help, they were not swayed in their willingness to help through voluntary actions. The study found that altruistic beliefs result in altruistic attitudes, which are more concerned about the helpful action than the person being helped. Therefore, altruistic intentions may be nurtured, as they inspire individuals to help others, including the homeless people living in the Johannesburg central business district (CBD). Consequently, altruistic values, such as benevolence, are more important than the perceptions and attitudes people hold about the homeless people living in and around the city centre as these thoughts may change when volunteers acquire altruistic personality traits.
A research report submitted in fulfilment of the requirement for the degree Master of Arts in Community-based Counselling Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021